Pulmonary arterial hypertension secondary to adult-onset Still's disease: Response to cyclosporine and sildenafil over 15 years of follow-up. (2016) - Weatherald, Jason; Lategan, Johan; Helmersen, Doug
Abstract: Adult onset Still's disease (AOSD) is an autoimmune disease characterized by systemic inflammation and is a rarely reported cause of pulmonary arterial hypertension (PAH). We describe the clinical course of a 40-year-old woman who presented with PAH 19 months after a diagnosis of AOSD. Sildenafil and immunosuppressive therapy with cyclosporine resulted in clinical and hemodynamic improvement with long-term survival 15 years after her initial presentation of AOSD. We review the literature for published cases of PAH due to AOSD and discuss the potential mechanisms relating inflammatory diseases and PAH.